The Implementasi Nilai Pancasila Dalam Diri Seorang Mahasiswa - Al Ghifari, M. Abidzar; Hanif, Fatma; Dinanti, Dia Dara; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This article examines the implementation of Pancasila values in the life of a student. Pancasila, as the foundational ideology of Indonesia, plays a significant role in shaping the character, ethics, and behavior of students in their academic and social lives. The study explores how the five principles of Pancasila — belief in one God, a just and civilized humanity, the unity of Indonesia, democracy guided by the inner wisdom in the unanimity arising out of deliberations, and social justice for all — can be integrated into the daily lives of students. It also addresses the challenges students face in applying these values amidst contemporary social issues. The research emphasizes the importance of Pancasila in fostering national identity, tolerance, and civic responsibility. By reflecting on real-life examples and theoretical frameworks, this article aims to highlight how Pancasila can guide students in developing strong ethical values, contributing to both personal growth and societal development. Ultimately, the implementation of Pancasila values is crucial in nurturing students who are not only academically competent but also responsible, ethical, and socially conscious citizens.